On μ-scale invariant operators - Tsekanovskii, E.; Makarov, K. A. (Methods of Functional Analysis and Topology, 2007)
We introduce the concept of a μ-scale invariant operator with respect to a unitary transformation in a separable complex Hilbert space. We show that if a nonnegative densely defined symmetric operator is μ-scale invariant for some μ>0, then both the Friedrichs and the Krein-von Neumann extensions of this operator are also μ-scale invariant.